Rapid Particle Size Measurements Used as a Proxy to Control Instant Whole Milk Powder Dispersibility - Boiarkina, I; Depree, N; Yu, W; Wilson, D; Young, B (Springer, 2016)
Characterising the dispersion of instant whole milk powder (IWMP) into water is a complex dissolution measurement that is both manual and laborious so is normally carried out post production at industrial dryers. However, this means there is no immediate feedback so the functional quality cannot be controlled in real-time. This work proposes the idea of applying a simpler, surrogate measurement that can be implemented in the plant in order to have useful real-time information regarding the quality of the product being produced. This we term is a proxy measurement. The functional property dispersibility was used as a case study, with particle size being investigated as a proxy at an industrial IWMP plant. It was found that particle sizing could be used to provide useful information regarding the powder, with the proxy measurement being able to predict in-specification powder 97% of the time. Although the test was not as effective for predicting out-of-specification results, with an false-positive rate of 50%, the fact that out-of-specification events are rare in the industry setting means that the overall proxy measurement is still between 78—87 % accurate, and thus useful for predicting the dispersibility quality of the IWMP. Furthermore, these proxy measurements can then be combined with on-line plant information using multivariate techniques to further improve their accuracy and understand how the quality can be controlled by changing the plant processing conditions.
Keywords: Quality; Dairy; Real time; Proxy measurement; Functional properties